PENGEMBANGAN E-EVALUASI PEMBELAJARAN BERBANTUAN WORDWALL PADA MATA PELAJARAN IPAS MATERI INDONESIAKU KAYA BUDAYA: Penelitian Research and Development - Rahma Alfiani Islamia; Yuli Mulyawati; Rini Sri Indriani (STKIP Subang, 2025)
This study uses the Research and Development (R&D) approach with the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The subjects of the study were students of grade IV of Cipatat State Elementary School, Bogor Regency, consisting of 20 students, the study was conducted in the even semester of the 2024/2025 school year. The purpose of this study was to develop and determine how to test the feasibility of the Development of E-Evaluation Assisted by Wordwall in the learning process in the classroom. The results of the study showed that the Development of E-Evaluation Assisted by Wordwall has a feasibility criterion of